The Social Construction of the Myth of Paddy Goddess in Sundanese Culture - Stephanus Djunatan (UIN Sunan Gunung Djati, 2024)
This research aims to find a sociological understanding of the Mother Earth myth in the Sundanese tradition in West Java, Indonesia. Based on an intercultural approach in philosophy, researchers combine cross-disciplinary analysis, namely philosophy, sociology and anthropology. This combination of interdisciplinary studies complements methods of interpreting texts and contexts regarding cognitive understanding, especially the principles of reasoning about meaningful worldviews in everyday life. The results of this interpretation are principles of reasoning or logic called functional logic. This argument about the logic of function starts from two layers of interpretation of two elements in the culture of agrarian society. The first element is the mythology of the Paddy Goddess, and the second element is the mythical figure of the Paddy Goddess, which is the main symbol in the description of rice cultivation. These two elements contain an understanding of the paradoxical relationship between two aspects that combine with each other in the management and structuring of the agricultural world. These two aspects are found in parental culture: father and mother. This study presents the interpretation of the text and context of the mythology and symbols of the Paddy Goddess and the practice of rice cultivation. Interpretation of mythology, the symbol of Paddy Goddess and rice cultivation requires a synchronic approach and emic analysis to conclude the implied meaning, namely the principle of function as the core meaning implied in the mythology of Paddy Goddess and Rice cultivation. This interpretation shows that logic functions as the main principle of reasoning that combines various cultural elements into a logical and meaningful 'way of seeing' the life world, which influences Sundanese people consciously or not in experiencing their culture in a logical and meaningful way.